Modulación multiportadora OFDM - Jiménez Cano, Leonardo; Parrado Galeano, José Joaquín; Quiza Montaña, Carlos Armando; Suárez Fajardo, Carlos Arturo (Ingeniería, 2000)
This paper presents an overview of multiple carrier modulation technique know as OFDM (Orthogonal Frequency Division Multiplexing). A discussion of the importance of orthogonality, the use of different modulation schemes which could be used to modulate the data at a low bit rate onto each carrier (mapping), the Fast Fourier Transform (FFT) for modulation and demodulation OFDM and the addition of the guard interval used to avoid intersymbol interference (ISI) caused by multipath distortion is reviewed.>